The Effect of Using Short Stories on Students’ Vocabulary Development at MTs Al Muttaqin Pekanbaru - Elfina, Yenti; Syahputra, Idham (State Islamic University of Sultan Syarif Kasim Riau, 2024)
Vocabulary is one of the important aspects in English to develop the ability of speaking, listening, reading and writing in learning English. The purpose of this research to examine whether or not there is significant effect of using short stories on students’ vocabulary development at MTs Al-Muttaqin Pekanbaru. The design of this research was quantitative data with the Pre-experimental design. The total of population were 272 students. The data of this research were collected from 34 students with the purposive sampling. The researcher taken one class in this research was class VIII A as experimental group. The technique of collecting data was Pre-test and Post-test design. The data analysis in this research by using statistical method of non parametric Wilcoxon signed rank test. The score analyze using was SPSS 23.0 version. The result of Wilcoxon test statistics, the value of Asymp. Sig (2-tailed) was 0.000. The result data can be seen that 0.000<0.05, it can be conclude that the hypothesis is accepted in experimental class used pre-test and post-test. The result of data analysis showed there was significant difference of the students’ vocabulary development before and after being taught using short stories at MTs Al-Muttaqin Pekanbaru.